2022
DOI: 10.3389/fimmu.2022.761225
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Tissue and Single Cell Transcriptome/Proteome Studies of the Brain in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory demyelinating and degenerative disease of the central nervous system (CNS). Although inflammatory responses are efficiently treated, therapies for progression are scarce and suboptimal, and biomarkers to predict the disease course are insufficient. Cure or preventive measures for MS require knowledge of core pathological events at the site of the tissue damage. Novelties in systems biology have emerged and paved the way for a more fine-grained understanding of key pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Therefore, results from our bioinformatics approach further confirmed such alterations of these biological processes in human ex vivo MS WM tissues. Similarly, a systematic review of proteomic studies reported several imbalances of WM proteostasis in MS brains [38], as seen in our study, although these reports showed some inconsistencies that were most likely due to the clinical heterogeneity of the disease. KEGG analyses also revealed alterations in pathways associated with insulin resistance.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, results from our bioinformatics approach further confirmed such alterations of these biological processes in human ex vivo MS WM tissues. Similarly, a systematic review of proteomic studies reported several imbalances of WM proteostasis in MS brains [38], as seen in our study, although these reports showed some inconsistencies that were most likely due to the clinical heterogeneity of the disease. KEGG analyses also revealed alterations in pathways associated with insulin resistance.…”
Section: Discussionsupporting
confidence: 72%
“…pVal<0.05, baseMean>10 -Figure 1F). As an@cipated from earlier studies, pathway analysis using the KEGG database on upregulated genes iden@fied ac@va@on of the IL17-, TGF-beta-, NFkappaB-, and MAPK-pathways as well as genes associated with hypoxia (Elkjaer et al, 2022) (Sup. Figure 1B).…”
Section: A Subset Of Ms Pa%ents Displays Extensive Transcrip%onal Der...mentioning
confidence: 96%
“…A recent review summarized CNS transcriptomics studies in multiple sclerosis ( Elkjaer et al, 2022 ). For example, RNA-seq of a large number of white matter MS lesions provided molecular profiling for distinct lesion types and identified TGFBR2 as major common hub mostly upregulated in remyelinating lesions ( Elkjaer et al, 2019 ; Table 1 , GSE138614).…”
Section: Transcriptomics Of Cns Tissues Under Physiology and Diseasementioning
confidence: 99%